Human Development Report 2021/2022 - United Nations Development Programme (United Nations, 2022)
Continuing the thread of the 2019 and 2020 Human Development Reports (HDRs), the 2021/2022 HDR carries forward a conversation centered on inequalities while integrating other important themes related to uncertainties in the Anthropocene: societal-level transformations, mental health impacts, political polarization, but also, crucially, opportunity. The Report explores how uncertainty in the Anthropocene is changing, what is driving it, what it means for human development, and how we can thrive in spite of it. The Report argues that, in the end, doubling down on human development is central to a more prosperous future for all.